Assessment of initial vancomycin dosing in neonates. Issue 6 (1st June 2014) - Dersch-Mills, Deonne; Bengry, Tanner; Akierman, Albert; Alshaikh, Belal; Yusuf, Kamran
Abstract: BACKGROUND: Vancomycin is recommended for optimal treatment of late-onset sepsis caused by coagulase-negative Staphylococcus in neonates. OBJECTIVES: To assess the performance of an empirical vancomycin dosing regimen in achieving target trough levels, and to revise this regimen if needed. METHODS: Data regarding doses and levels were collected and pharmacokinetic parameters were calculated, where possible, for neonates receiving vancomcyin in a neonatal intensive care unit. The primary measure was the percentage of neonates with initial prevancomycin levels of <10 mg/L, 10 mg/L to 20 mg/L and >20 mg/L. Secondary measures included the percentage of neonates with extrapolated trough levels in these ranges, total daily doses that achieved target levels (10 mg/L to 20 mg/L) and total daily doses/dosing intervals that were pharmacokinetically predicted to achieve trough levels of 15 mg/L. RESULTS: Of 153 infants started on the empirical regimen (15 mg/kg/day to 45 mg/kg/day, depending on postnatal age and weight), 34.2% initially achieved target trough levels (mean 8.7 mg/L). Analysis of actual doses and pharmacokinetically predicted doses required to reach target levels suggested increasing the empirical dosing for all neonatal age groups. The revised regimen used in the present study (20 mg/kg/day to 40 mg/kg/day, depending on postmenstrual age and postnatal age) was predicted to result in 72% of infants achieving initial target trough levels (mean 15.4 mg/L). CONCLUSIONS: A revised empirical vancomycin dosage regimen for neonates was required based on poor achievement of target trough levels (10 mg/L to 20 mg/L) using the previous regimen. The modified regimen is predicted to reach target trough levels more often and increase the mean initial trough levels achieved. This regimen requires clinical validation in an independent cohort in the future.